2019
DOI: 10.2147/ott.s190934
|View full text |Cite
|
Sign up to set email alerts
|

<p>FAM111B, a direct target of p53, promotes the malignant process of lung adenocarcinoma</p>

Abstract: Purpose: Lung adenocarcinoma (LUAD) is a main subtype of lung cancer, which is the leading cause of cancer-related deaths. The five-year survival rates of lung cancer patients are still comparatively low. Therefore, potential therapeutic targets are urgently needed to improve the survival of lung cancer patients. In this study, we identified FAM111B as an oncogene and potential therapeutic target for LUAD. Methods: The TCGA database and tissue microarray analysis were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 27 publications
(26 reference statements)
6
65
0
Order By: Relevance
“…Interfering with FAM111B inhibited the proliferation, cell cycle arrest and migration of LUAD cells and the ability of tumor formation in nude mice, but induced apoptosis. FAM111B might regulate the growth of LUAD through p53 signaling pathway, inhibit the expression of BAG3 and BCL2, and play an important role in cell cycle and apoptosis [21]. In present study, we found that MTFR2 coexpressed genes were mainly involved in cell cycle, DNA replication, homologous recombination, p53 signaling pathway and other signaling pathways by KEGG.…”
Section: Screening Of Mtfr2 Co-expressed Genessupporting
confidence: 48%
“…Interfering with FAM111B inhibited the proliferation, cell cycle arrest and migration of LUAD cells and the ability of tumor formation in nude mice, but induced apoptosis. FAM111B might regulate the growth of LUAD through p53 signaling pathway, inhibit the expression of BAG3 and BCL2, and play an important role in cell cycle and apoptosis [21]. In present study, we found that MTFR2 coexpressed genes were mainly involved in cell cycle, DNA replication, homologous recombination, p53 signaling pathway and other signaling pathways by KEGG.…”
Section: Screening Of Mtfr2 Co-expressed Genessupporting
confidence: 48%
“…3A ). In the list of lung_NSC cell lines with high expression of FAM83A, the common LUAD cell line, NCIH1650, has been used for research in a previous study ( 18 ) and was selected for subsequent experiments ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, overexpression of MTL5 was reported in NSCLC, and its expression was shown to predict prognosis [38]. Another study showed that knockdown of FAM111B induced G 2 /M phase arrest and apoptosis in LUAD cells [39]. These data suggested that miR-143-5p -controlled genes were closely involved in LUAD oncogenesis and molecular pathogenesis.…”
Section: Discussionmentioning
confidence: 99%